NASIONALISME-KEDAULATAN DALAM VISI PRESIDEN KE-1 SOEKARNO DAN PRESIDEN KE-8 PRABOWO SUBIANTO - Sabarudin, Didin (JURNAL KEBANGSAAN RI, 2024)
Nationalism and sovereignty are two words that are always attached to two figures of Indonesian national leaders, namely the 1st President Soekarno and the 8th President Prabowo Subianto. The nationalism and sovereignty echoed by the two Presidents are based on the empirical objective conditions faced by the Indonesian nation in the form of nationale geest (national spirit), nationale will (national will), and nationale daad (national action). Soekarno implemented nationalism and sovereignty based on the trisakti philosophy transformed by Prabowo Subianto during his administration with the symbol "Indonesia first, make Indonesia great again" as the identity of the internal sovereignty project and external sovereignty: "Si Vis Pacem Para Bellum and I want to be your friend, I want to be your partner, but I can not be your peon". This study captures and elaborates nationalism-sovereignty of Soekarno and Prabowo Subianto through a study of documentation literature. The historical method with a qualitative approach is used to interpret the implementation of nationalism-sovereignty through the vision of Soekarno and Prabowo Subianto. The results of the study show that nationalism and sovereignty are the characteristics of national ideology as well as legitimate identity in Soekarno and Prabowo Subianto so that they received international recognition in the form of the 20th century Memory of the World for Soekarno’s Speech before the UN General Assembly in 1961 for Soekarno and Prabowo Subianto including one of the most influential Muslim figures in the world in 2023